ENGLISH LANGUAGE TEACHING AND LEARNING DEVELOPMENTS - Kamola Nasirovna Kayumova (American Journals, 2023)
This article talks about modern methods and ways of teaching English
Keywords: foreign language, methods, process, oral and written speech lesson, learning conditions